More agile testing learning journeys for the whole team - Gregory, Janet 1953- (Addison-Wesley, 2015)
Janet Gregory and Lisa Crispin pioneered the agile testing discipline with their previous work, Agile Testing . Now, in More Agile Testing, they reflect on all they've learned since. They address crucial emerging issues, share evolved agile practices, and cover key issues agile testers have asked to learn more about. Packed with new examples from real teams, this insightful guide offers detailed information about adapting agile testing for your environment; learning from experience and continually improving your test processes; scaling agile testing across teams; and overcoming the pitfalls of automated testing. You'll find brand-new coverage of agile testing for the enterprise, distributed teams, mobile/embedded systems, regulated environments, data warehouse/BI systems, and DevOps practices. You'll come away understanding " How to clarify testing activities within the team " Ways to collaborate with business experts to identify valuable features and deliver the right capabilities " How to design automated tests for superior reliability and easier maintenance " How agile team members can improve and expand their testing skills " How to plan "just enough," balancing small increments with larger feature sets and the entire system " How to use testing to identify and mitigate risks associated with your current agile processes and to prevent defects " How to address challenges within your product or organizational context " How to perform exploratory testing using "personas" and "tours" " Exploratory testing approaches that engage the whole team, using test charters with session- and thread-based techniques " How to bring new agile testers up to speed quickly-without overwhelming them The eBook edition of More Agile Testing also is available as part of a two-eBook collection, The Agile Testing Collection (9780134190624)
Includes bibliographical references and index. - Print version record
Keywords: Computer software -- Testing; Agile software development; Méthodes agiles (Développement de logiciels); Computer software; Testing